2020
DOI: 10.1371/journal.pone.0229568
|View full text |Cite
|
Sign up to set email alerts
|

The presence of coexisting sleep-disordered breathing among women with hypertensive disorders of pregnancy does not worsen perinatal outcome

Abstract: ObjectiveTo determine whether the presence of co-existing sleep-disordered breathing (SDB) is associated with worse perinatal outcomes among women diagnosed with a hypertensive disorder of pregnancy (HDP), compared with normotensive controls. Study designWomen diagnosed with HDP (gestational hypertension or preeclampsia) and BMI-and gestation-matched controls underwent polysomnography in late pregnancy to determine if they had coexisting SDB. Fetal heart rate (FHR) monitoring accompanied the sleep study, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 49 publications
0
15
1
Order By: Relevance
“…These data are a secondary analysis of two prospective case–control studies with similar protocols but different patient groups, investigating the impact of SDB during pregnancy on fetal health, between 2012 and 2018 (Wilson et al . 2020; Skrzypek et al . 2021).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…These data are a secondary analysis of two prospective case–control studies with similar protocols but different patient groups, investigating the impact of SDB during pregnancy on fetal health, between 2012 and 2018 (Wilson et al . 2020; Skrzypek et al . 2021).…”
Section: Methodsmentioning
confidence: 99%
“…These data are a secondary analysis of two prospective case-control studies with similar protocols but different patient groups, investigating the impact of SDB during pregnancy on fetal health, between 2012 and 2018 (Wilson et al 2020;Skrzypek et al 2021). Specifically, the cases in these studies had an HDP which included gestational hypertension, preeclampsia or chronic hypertension (Tranquilli et al 2014) or FGR which met the Delphi consensus criteria (likely to be caused by placental insufficiency, based on estimated fetal weight or abdominal circumference <3rd centile, or estimated fetal weight or abdominal circumference <10th centile with abnormal fetoplacental Dopplers on ultrasound (Gordijn et al 2016).…”
Section: Participantsmentioning
confidence: 99%
See 2 more Smart Citations
“…The relationship between objective measures of mild OSA and birth weight has been hardly studied with mixed results and remains currently unclear. Some studies suggest that maternal OSA in pregnancy (even in a mild form) is associated with reduced fetal growth in late pregnancy (14), and with an increased risk of delivering a small-for-gestationalage infant (52), while other studies showed contrasting findings (56)(57)(58). Such inconsistencies may relate to differences in sample characteristics with heterogeneous populations, with inadequate control on confounders, such as pre-gestational BMI and pregnancy complications, and methodological differences in terms of sleep assessment procedures, as well as timing of sleep evaluation.…”
Section: Inflammatory Profile and Pregnancy And Neonatal Outcomesmentioning
confidence: 99%